Recent developments in conducting polymers: applications for electrochemistry. Issue 62 (13th October 2020) - Tajik, Somayeh; Beitollahi, Hadi; Nejad, Fariba Garkani; Shoaie, Iran Sheikh; Khalilzadeh, Mohammad A.; Asl, Mehdi Shahedi; Van Le, Quyet; Zhang, Kaiqiang; Jang, Ho Won; Shokouhimehr, Mohammadreza
Abstract : Scientists have categorized conductive polymers as materials having strongly reversible redox behavior and uncommon combined features of plastics and metal. Abstract : Scientists have categorized conductive polymers as materials having strongly reversible redox behavior and uncommon combined features of plastics and metal. Because of their multifunctional characteristics, e.g., simplistic synthesis, acceptable environmental stability, beneficial optical, electronic, and mechanical features, researchers have largely considered them for diverse applications. Therefore, their capability of catalyzing several electrode reactions has been introduced as one of their significant features. A thin layer of the conducting polymer deposited on the substrate electrode surface can augment the electrode process kinetics of several solution species. Such electrocatalytic procedures with modified conducting polymer electrodes can create beneficial utilization in diverse fields of applied electrochemistry. This review article explores typical recent applications of conductive polymers (2016–2020) as active electrode materials for energy storage applications, electrochemical sensing, and conversion fields such as electrochemical supercapacitors, lithium-ion batteries, fuel cells, and solar cells.